PENGARUH LAYANAN BIMBINGAN KLASIKAL DENGAN TEKNIK ROLE PLAY TERHADAP KEMAMPUAN REGULASI EMOSI SISWA KELAS VII G SMP NEGERI 7 MADIUN - Angraini, Elisa Putri; Christiana, Ratih; Oktriani, Endah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of classical guidance services using the role-play technique on the emotional regulation abilities of Grade VII G students at SMP Negeri 7 Madiun. Emotional regulation is an individual's ability to recognize, manage, control, and express emotions appropriately in response to the situation at hand. Low emotional regulation skills among junior high school students are often manifested through irritability, conflicts with peers, difficulty controlling emotions, and a lack of ability to understand others' feelings. One service that can be utilized to improve emotional regulation is classical guidance incorporating the role-play technique. This technique provides students with the opportunity to enact specific social situations, thereby enabling them to understand others' perspectives, develop empathy, and practice emotional control. The study employed a quantitative approach using a quasi-experimental method with a pretest-posttest control group design. The sample consisted of 12 students, divided into an experimental group and a control group of 6 students each. An emotional regulation scale served as the research instrument. Data analysis was conducted using descriptive statistics and the Independent Sample t-test. The results indicate a significant difference between the experimental group and the control group following the intervention. The significance value of 0.000 was lower than α = 0.05; thus, the research hypothesis was accepted. These findings demonstrate that classical guidance services using the role-play technique have an impact on improving students' emotional regulation abilities.